Understanding the mechanism of actions of 1A calcidol on arterial stiffness, microvascular endothelial function, inflammation and proteinuria in Type 2 Diabetic patients with nephropathy - Rasool, Aida Hanum Ghulam (Universiti Sains Malaysia, 2014)
Introduction: Low vitamin D levels correlate with presence of cardiovascular diseases (CVD) in diabetics. Mechanism for the beneficial effects of vitamin D on CVD has not been fully explained. This study aimed to evaluate possible mechanisms for vitamin D effects on markers linked to CVD progression. The effects of vitamin D (as 1-alfacalcidol) in diabetic nephropathy patients on i) arterial stiffness ii) microvascular endothelial function iii) inflammation iv) proteinuria were evaluated. Methodology: A prospective randomized controlled study was conducted in diabetic nephropathy patients. Vitamin D treated group (n=28) were given la calcidol 0.25 meg daily for 6 months, while control patients (n=32) received standard treatment. Baseline measurements for vitamin D levels, hsCRP, arterial stiffness, blood pressure (BP), microvascular endothelial function, renal function and albuminuria were performed and repeated after 6 months. Results and conclusion: After 6 months treatment with vitamin D, there was significant improvement in arterial stiffness in vitamin D deficient patients. Significant reductions in central SBP, central pulse pressure and peripheral SBP were also observed. Microvascular endothelial function was impaired in vitamin D deficient diabetic nephropathy patients, however, 6 months treatment with 0.25 meg alfacalcidol did not improve this parameter. Systemic inflammation increased after 6 months in controls patients but was not seen in vitamin D treated patients. It appears that the effects of vitamin D on CV markers were more apparent in vitamin D deficient diabetic nephropathy patients. Thus, vitamin D may be beneficial for CVD via its effect of improving BP, arterial stiffness, microvascular function and delaying progression of inflammation in diabetic nephropathy patients.